2x+16=-7x-11

Simple and best practice solution for 2x+16=-7x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+16=-7x-11 equation:


Simplifying
2x + 16 = -7x + -11

Reorder the terms:
16 + 2x = -7x + -11

Reorder the terms:
16 + 2x = -11 + -7x

Solving
16 + 2x = -11 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
16 + 2x + 7x = -11 + -7x + 7x

Combine like terms: 2x + 7x = 9x
16 + 9x = -11 + -7x + 7x

Combine like terms: -7x + 7x = 0
16 + 9x = -11 + 0
16 + 9x = -11

Add '-16' to each side of the equation.
16 + -16 + 9x = -11 + -16

Combine like terms: 16 + -16 = 0
0 + 9x = -11 + -16
9x = -11 + -16

Combine like terms: -11 + -16 = -27
9x = -27

Divide each side by '9'.
x = -3

Simplifying
x = -3

See similar equations:

| -4=4w+4 | | -3((x^-2yz^4)/(7x^2y^-3z))^6 | | (3x-3)(6x+7)=0 | | 50m^3-32m=0 | | 3X(1/4) | | 2y+41=1201 | | x+4.6=7.6 | | 5x-15+y+4x+5=90 | | 6n+2n=2(3n-6)-(3n+3) | | y+0=4 | | 1.1750=70x | | y+-1=4 | | 2d^3-50d=0 | | 6/5x=-30 | | -8-6(-2x+1)=-(-2x+9)-6 | | y+-2=4 | | 8-6x=y | | 1=0.3x-0.6x-8 | | 3x(78a-9)= | | 2x^3-12x^2-36x+192=0 | | 3(-1.4+b)-2b=8b-7-2(-1.4+b) | | x-3/9=4/9 | | .05x+50=.15x+10 | | u^2-6uv-27v^2= | | 4u/5=40 | | -8x-4=3(x+6) | | 2n+5=n-1 | | 6x+12=28-4x | | 2x+10+58+92=180 | | 3x^2+16x+10=0 | | 7x^2+24-16=0 | | 9d^2-64=0 |

Equations solver categories